ANALISIS HUBUNGAN PENERAPAN PESAN GIZI SEIMBANG KELUARGA DAN PERILAKU KELUARGA SADAR GIZI DENGAN STATUS GIZI BALITA DI PROVINSI KALIMANTAN BARAT - Didik Hariyadi; M. Rizal Damanik; Ikeu Ekayanti (Jurnal Gizi dan Pangan, 2010)
The present study aims to analyze of relationship of the implementation of balanced nutrition messages family and behavior family nutrition awareness with under five years child nutritional status in West Kalimantan Province. The study uses Health Research Data Base of West Kalimantan Province in year 2007 with the design of cross-sectional study. The total of 1992 household samples were recruited in the study with criteria having child aged 6 to 59 months. Weight for height, weight for age and height for age indicators were used to measure child nutritional status. The results showed that three messages did not meet criteria as required by the Indonesian Food Guideines. Three messages did not meet criteria as required by the Indonesian Food Guidelines. They were eat food withr energy needs requaired, eat half of food sources of carbohydrate for energy needs and eating one of  fourth of food sources of fat for energy needs. Logistic multiple regression analysis showed that failure to follow the the Family Nutrition Awareness had 1.21 risk for children to became stunting than family to follow to guideline properly.